Core Thinking skills for the kindergarten children, according to some variables (Journal Of Educational and Psychological Researches, 2012)
The study aimed at the following:    Identify the differences in average scores core  thinking skills kindergarten children by variable sex (male - female), and by variable age (5.6 - 5.11).To achieve this researcher adopted a standardized test of core thinking skills for the kindergarten children, which was built and standardization by the researcher Meyada Asaad Mussa 2012 . applied test on a sample of (814) ) boys and girls who were randomly chosen form,  from directorates of Baghdad Education Adoption of the proportional distribution.     Was shown there are differences between males and females in some of the core thinking skills. While not shown the skills the remaining differences between males and females.   As shown there are differences in some of the core thinking skills as the variable age (5.6 -  5.11). While not shown the skills the remaining differences betweenage(5.6-5.11)